Common diseases alter the physiological age-related blood microRNA profile - Tobias Fehlmann (Nature Portfolio, 2020)
Aging is a key risk factor for chronic diseases of the elderly. Here the authors perform large-scale miRNA profiling of blood from individuals of a range of ages and show that common diseases alter the physiological age-related blood microRNA profile.